The Association Between Maternal Attachment Styles and Dyadic Synchrony: Exploring a Home Visiting Program for Young Mothers - Staver, Alexis. (2017)
Abstract: Using data from the Massachusetts Healthy Families Evaluation Early Childhood study, this thesis explored the association between maternal attachment style dimensions and dyadic synchrony in a diverse sample of young mothers (n = 312) enrolled in Healthy Families Massachusetts, a newborn home visiting program for first time mothers under the age of 21. Group differences in attachment style dimensions and dyadic synchrony between mothers receiving home visits (HVS) and mothers receiving referral information only (RIO) were examined. Results revealed significant group differences in maternal attachment style dimensions, demonstrating that RIO mothers had higher scores on insecure attachment style dimensions compared to HVS mothers. There were no significant group differences in dyadic synchrony scores and a non-significant relation between maternal attachment style dimensions and dyadic synchrony. Findings can be used to encourage intervention programs to increase services specifically for young mothers that improve parent-child interactions and promote positive parenting practices.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Child Study and Human Development.; Advisor: Ellen Pinderhughes.; Committee: Jana Chaudhuri, and Alexander Queen.; Keyword: Psychology.